The Application of the Best Interest of the Child Principle as a Basis for Determining Child Custody - Angela Melani Widjaja; Ike Yeni Kartika Sari; Hasna Firaz Isza Fadhilah; Devi Sukma Ayuningtyas (Faculty of Law, University of Mataram, 2020)
This research was conducted to introduce the principle of the best interest of the child as a basis for judges to create decisions regarding the child custody that reflects child protection. Based on this idea, the problem formulations in this research are: First of al, what is the basis for determining child custody by judges in Indonesia? and Secondly, what is the basis for determining child custody that reflects the principle of The Best Interest of The Child This paper is legal research which applies statute approach, conceptual approach, and case approach. Based on this research, it was found that Firstof all, there are differences for judges in determining child custody in Indonesia for Muslim and non-Muslim couples. For Muslim couples, if the child is 12 (twelve) years old and over, the custody of the child is prioritized to be handed to the mother and if the child is under 12 (twelve) years of age, then custody will be given to the mother. For non-Muslim couples, generally, the custody of the child will be prioritized to be given to the mother. Secondly, The basis for determining the provision of child custody that reflects the principle of the best interest of the child for Muslim couples is that if the child is over 12 (twelve) years old, therefore the judge should not necessarily prioritize giving custody to the mother, rather they must pay attention to aspects of the need and the wishes of the child. If the child is not yet 12 (twelve) years old, the judge should also consider the desires and needs of the child and not necessarily give custody to the mother. The basis for determining the granting of child custody that reflects the principle of the best interest of the child for non-Muslim couples is when the judge does not necessarily give priority to the mother, but should consider the desiresand needs of the child.